A statement of the number of free white tythables in each of the counties and corporations of this Commonwealth, for the years 1840 and 1844 (House document (Virginia. General Assembly. House of Delegates) ;, 1845)
January 21, 1845 Auditor's statement of the number of free white tithables in each county and corporation of the Virginia Commonwealth for 1840 and 1844, in compliance with a House resolution so requiring.